ANALISIS HUBUNGAN ANTARA BETA, STRUKTUR MODAL, UKURAN PERUSAHAAN DENGAN RETURNS SAHAM - Sofiati -; Yenni Kurnia Gusti (Trunojoyo University of Madura, 2014)
This research extends previous research In portofolio theory turns out that inaddition to beta stocks it turns out the size and the debtan be used as a measure of riskof stock risk. This sudy was conducted to examine whether there are other factorsbesides beta stock that affect returns.this research extends previous study in portfoliotheory describe that beta...This study using two step model. First, this research use as 55 of sample ofpublicfirms and listed in 2009 – 2013 within used a capital assets pricing models forfinding some value havea sigmificant positivebetha on 55 samples of public fimrs. Thisresearch founds that 47 samples have a significant positive in betha.Second, on this step method not use some 55 samples of publication firms but using of47 samples of publication from first method. On second step method wants to know thatDebt Equity Ratio with common stock return have a relationship. Some values such asbetha and size used by control variables. This research found that Debt and commonstock return hava positive significants relationship.